Vietnam pocket guide - Forbes, Andrew; Emmons, Ron (Berlitz Publishing, 2019)
Berlitz Pocket Guide VietnamThe world-renowned pocket travel guide by Berlitz, now with a free bilingual dictionary.Compact, concise and packed full of essential information about where to go and what to do, this is an ideal on-the-move guide for exploring Vietnam. From top tourist attractions like Ho Chi Minh City, Cham Towers and Hanoi, to cultural gems, including the ornate assembly halls of Hoi An, the unmissable Halong Bay and the colourful Cao Dai Temple, plan your perfect trip with this practical, all-in-one travel guide.